Activity of Caprine CSN1S2 Protein Reducing the COX-2 and IL-17 Expression of Aorta Tissue in Type 2 Diabetes Mellitus Rat - Yoga Tribakti Rachmad; Titin Andri Wihastuti; Katsuhiro Miyajima; Fatchiyah Fatchiyah (Institute for Research and Community Services (LPPM) ITB, 2018)
Type 2 diabetes mellitus (T2DM) is a degenerative disease that leads to increased inflammation and cyclooxygenase protein production, which causes tissue abnormalities. The aim of this study was to determine the effect of caprine CSN1S2 protein against abnormal metabolic pathways in the aorta of DM rats. The twenty-four-animal model was control, diabetes and treatment groups. Histopathological evaluation of the aortic tissue by hematoxylin eosin staining. The expression of cyclooxygenase and inflammatory cytokine was measured by western blotting. In the DM750 groups, the amount of discontinued-endothelial was significantly more reduced than in the other groups. The amount of macrophages in the DM1500- group decreased more than in the DM and DM375 groups. The amount of foam cells in the DM750 and DM1500 groups decreased more than in the DM group and was close to all control groups. The expressions of COX-2 and IL-17 were effectively reduced and vice versa the expression of IL-10 was increased in DM750 compared with the other groups. Meanwhile, COX-1 expression did not change in all groups. This study indicates that caprine CSN1S2 protein at a dose of 750 mg/kg BW has a significant effect on controlling, protecting, and repairing abnormalities in the aortic tissue of T2DM rats.